Racism and Gender Intersections Among Poor Urban Families The Role Of Inclusive Policies - Gomes, Cristina (Advances in Social Sciences Research Journal, 2018)
This article analyses how social policies affect the relationships of female beneficiaries with their partners, relatives, friends and neighbours in the Metropolitan Region of Salvador, Brazil. Relations between groups can involve gender discrimination, racism and social prejudices, which is understandable within the concept of intersectionality, in comparison to the framework of intergroup competition for scarce resources or according to the perspective of realistic intergroup conflicts. Methods: A qualitative methodology combined interviews with beneficiaries of Conditioned Cash Transfers programs (CCT) and other social programs, as well as with focus groups comprising of these beneficiaries, their relatives, friends and neighbours. Results: social programs have been able to reduce the impact of poverty and have improved gender empowerment and partners’ relationships within the families. However, prejudices and intergroup conflicts emerge between beneficiaries with small children and their friends or neighbours, (mainly childless women who applied but were not considered poor and do not receive social benefits). Discussion: Results confirm the hypothesis of realistic intergroup competition. Moreover, racism persists in poor communities, indicating that intersectionality should be included in the framework of affirmative policies and education to promote equality values should be reinforced in order to mitigate race discrimination and intergroup conflicts.